Effect of addition of surface water treatment sludge to biomass in biochar porosity - Silva, Francisco Raimundo da [UNESP]; Nozela, Weverton Campos [UNESP]; Dias, Diogenes Dos Santos [UNESP]; Almeida, Sonia [UNESP]; Crespi, Marisa Spirandelli [UNESP]; Ribeiro, Clovis Augusto [UNESP] (Springer, 2019)
Samples of pruning sawdust (PS) and water treatment plant (WTP) sludge residue were collected and mixed in proportions of 10 to 80% of WTP sludge in PS, submitted to torrefaction at 260 degrees C, and the resulting biochar samples were submitted to TG/DTG analysis to assess their decomposition, thermal stability, and immediate analysis. Also, the nitrogen adsorption-desorption isotherm, mercury-injection capillary pressure (MICP), ultimate analysis, SEM, EDS, and FTIR were employed. The biochars of blend with 20% of sludge (BB20) and PS without sludge (BBM) were the ones that presented the best stability test in an aqueous medium. The biochar BB20 presented thermal stability (190 degrees C), moisture (5.7%), volatiles (48.6%), fixed carbon (35.9%), ash (9.8%), BET surface area (0.7942 m(2) g(-1)), mean pore diameter (389.13 angstrom), adsorption-desorption isotherm characteristic of the mesoporous material, highest MICP total pore volume, porosity (76.7%), total pore area (62.859 m(2) g(-1)), mean pore diameter (0.1322 mu m), the predominance of macropores. The biochar BBM showed BET surface area (1.3366 m(2) g(-1)), mean pore diameter (169.97 angstrom), adsorption-desorption isotherm characteristic of mesoporous material, better second one MICP total pore volume, porosity (64.4%), total pore area (76.520 m(2) g), mean pore diameter (0.0786 mu m) also, macroporosity. According to the results presented, the biochar BB20 itself to several uses as substitution of anthracite coal in water and filtration systems plant for the wastewater treatment due to macroporosity and as a viable solution to the reuse of these two residues.
Keywords: Biochar; Torrefaction; Sustaintability; Porosity